The Concept of Literacy in the Qur'an, Surah Al-'Alaq, Verses 1-5 - Asep Sobirin; Hafid; Cecep Anwar (al-Afkar, Journal For Islamic Studies, 2026)
This research is an effort to examine the concept of literacy within the content of the Qur'an, Surah Al-'Alaq verses 1-5, based on the explanations of Tafsir scholars (Mufassir) and the views of previous researchers who have discussed the content of these verses using various approaches and different titles. This study employs a qualitative approach by applying a descriptive method, incorporating concepts and theories. From the results of this examination, it can be concluded that the content of the Qur'an in Surah Al-'Alaq verses 1-5 contains the concept of literacy, namely reading and writing. The first verse, "Read in the name of your Lord who created," and the third verse, "Read, and your Lord is the Most Generous," convey a command to read, while the fourth verse, "Who taught by the pen," conveys a command to write.